Review paper on thermal expansion and tribological behavior of composite materials. (2023) - Verma, Abhishek; Singh Chauhan, Shailendra; Prakash Dwivedi, Shashi
Abstract: Composite materials are cutting-edge materials with uncontrollable opportunities for modern development and material research. The designer will get help from these materials to accomplish objectives and desired conceptions. The reinforcement of metals serves as a tool to satisfy the various objectives of different metals. The use of light metals for reinforcement opens up a world of possibilities for weight reduction. Traditional materials become motivating for usage as constructional and functional materials if their property contours either do not satisfy the higher standards of explicit expectations or are the solution to the difficulty. Traditional materials, on the other hand, become motivating for usage as constructional and functional materials if their property contours either do not reach the growing standard of explicit expectations or are the solution to the problem. The appreciating knowledge of composite materials, on the other hand, competes with other contemporary material technologies. Researchers and scientists are now interested in and active in breakthroughs relevant to metal matrix composite materials. A large number of scientists and researchers have conducted considerable research. Light alloys are attractive as a basic matrix, according to literature, due to affordability, availability, and recycling. As basic matrixes, aluminium, copper, magnesium, iron metals, and titanium including their alloys, are commonly employed. The choice of a certain base matrix is influenced by the industrial uses of composites. Other alloys can be employed, but only for a limited number of applications.